A new strategy against endometriosis: Oral probiotic treatments. Issue 1 (2021) - Chouzenoux, S; Jeljeli, M; Bourdon, M; Doridot, L; Thomas, M; Barbeito, A; Daniel, C; Mousset, PY; Batteux, F; Nicco, C
No abstract available